No increased risk of relapse of breast cancer for women who give birth after assisted conception. Issue 4 (18th December 2019) - Rosenberg, E; Fredriksson, A; Einbeigi, Z; Bergh, C; Strandell, A
Abstract: STUDY QUESTION: Is childbirth after IVF associated with a risk of relapse in breast cancer? SUMMARY ANSWER: Women who had been diagnosed with breast cancer and completed treatment had no increased risk of relapse if they gave birth after conceiving with IVF. WHAT IS KNOWN ALREADY: Pregnancy and childbirth have not been shown to increase the risk of relapse in breast cancer. Ovarian stimulation during IVF increases the oestrogen levels and could theoretically increase the risk of relapse in breast cancer. STUDY DESIGN, SIZE, DURATION: This is a retrospective register study, using national Swedish register data from the National Patient Register, the Medical Birth Register, the Swedish National Cancer Register, the National Breast Cancer Register, the National Quality Registry of Assisted Reproduction (Q-IVF), the National IVF Dataset, the Swedish Prescribed Drug Register and the Cause of Death Register. All women diagnosed with breast cancer who were between 20 and 44 years of age during the years 1982 to 2014 and identified in the cancer registries were assessed. PARTICIPANTS/MATERIALS, SETTING, METHODS: Women, previously diagnosed with breast cancer, who had given birth after IVF (29 after completed breast cancer treatment and 8 after fertility preservation) were compared with a matched control group who had given birth after spontaneous conception. Matching was done in a ratio 1:4, based on T-stage (size of the tumour) and year of diagnosis +/−5 years. MAIN RESULTS AND THE ROLE OF CHANCE: We found 26 114 women that had been diagnosed with breast cancer when 20–44 years old and of those 860 had subsequently given birth, 823 after spontaneous and 37 after IVF conception. Follow-up time was similar between the groups, ranging from 2.6 to 24.0 years, with a mean follow-up time of 10.3 (SD 4.2) years in the IVF group and 10.7 (SD 4.4) years in the control group. There were no relapses (0/37) in the IVF group. The relapse rate for the matched controls was 36/148 (24.8%). Ten women who suffered relapse died due to breast cancer. LIMITATIONS, REASONS FOR CAUTION: This is reassuring data; however, the result is based on a few cases. The poor coverage of important prognostic variables in the register resulted in uncertain comparability of the groups. The main limitation in this study is the extent of missing data on tumour-related variables, due to poor coverage from the early years of the National Breast Cancer Register. It is possible that the women accepted for IVF had a less aggressive breast cancer and were generally healthier than women delivering after conceiving spontaneously and therefore had a lower risk of relapse. Other limitations are the lack of information on the anticancer therapies used and type of disease relapse, plus the older of the two IVF registers did not hold information on unsuccessful IVF cycles, leaving only cycles leading to birth, to be analysed. WIDER IMPLICATIONS OF THE FINDINGS: We found no indication that women who had been diagnosed with breast cancer had an increased risk of relapse if they gave birth after conceiving with IVF. Based on our findings, there is no evidence to advise against IVF treatment in this group of women. More detailed registry data would be valuable for future studies, enabling proper matching of tumour characteristics between groups. STUDY FUNDING/COMPETING INTEREST(S): The study was financed by grants from the Swedish state under the agreement between the Swedish government and the county councils, the ALF-agreement (ALFGBG-720291), The Assar Gabrielsson Fund (FB 15-20), The Breast Cancer Fund and the Swedish Association of Local Authorities and Regions, SKL. There are no conflicts of interest to declare.